EPHA2 promotes triple-negative breast cancer progression by suppressing pyroptosis via the AKT/PI3K/mTOR pathway - Xiaoying Huang; Li Na; Qingkai Han; Qilun Liu; Ligang Wu (Frontiers in Oncology)
BackgroundBreast cancer (BRCA) is the most prevalent cancer in women, with triple-negative breast cancer (TNBC) accounting for 15-20% of cases. TNBC is associated with higher rates of metastasis, recurrence, and poorer prognosis, underscoring the urgent need for new diagnostic and therapeutic strategies.MethodsIn this study, multiple public online platform, including UCSC Genome, UALCAN, Kaplan Meier plotter, DepMap and Single Cell Portal were used to detect the expression of EPHA2 in TNBC. Cell Counting Kit-8 (CCK-8) and transwell assays were conducted to assess proliferation and invasion. KOBAS bioinformatics, transmission electron microscopy (TEM), ELISA, western blot and quantitative real-time PCR experiments were employed to detect the association and effects of EPHA2 on pyroptosis in BRCA.ResultsEPHA2 was highly expressed in TNBC, and showed a negative correlation with survival. Single-cell analysis indicated that EPHA2 was mainly expressed in stromal and epithelial cells, particularly within TNBC compartments. Furthermore, we found that EPHA2 knockdown inhibited cell proliferation and invasion, and induced pyroptosis, as evidenced by increased level of pyroptosis-related protein (IL-18, IL-1β) and characteristic morphological changes. Moreover, a relationship between EPHA2, pyroptosis, and the AKT/PI3K pathway was established and confirmed. Additionally, we observed a decreased expression of ferroptosis-associated marker named SLC7A11, suggesting that this transporter may mediate the effects of AKT inhibition on pyroptosis.ConclusionsIn summary, our findings illuminated the dual roles of EPHA2 in TNBC, influencing both tumor progression and cell death pathways. We hypothesize that SLC7A11 serves as a key regulator of pyroptosis in the context of EPHA2 and AKT/PI3K signaling. These insights underscore the potential of targeting these pathways in developing therapeutic strategies for BRCA treatment. Further investigations into the mechanisms underlying SLC7A11’s roles could enhance our understanding of its therapeutic implications.